Inducing low energy availability in trained endurance male athletes results in poorer explosive power - Jurov, I.; Keay, N.; Spudic, D.; Rauter, S. (European Journal of Applied Physiology, 2022)
Purpose Low energy availability in males needs more original research to understand its health and performance consequences. The aim of the study was to induce low energy availability in previously healthy male endurance athletes by reducing energy availability by 25% for 14 consecutive days and measure any potential changes in performance, health, mental state or energy markers.